Analysis of a problem situation: socio-emotional competences and stimulation of executive functions - Alexandra Amadio Belli; Ana Lucia Manrique (Educação Matemática Debate, 2018)
The present study aims to analyze the experience of a problem situation in mathematics classes of the initial years of Elementary Education of a public school in the city of São Paulo linked to socio-emotional competences and problem solving. This research was conduct with three teachers of the initial years of Elementary Education. It was organized in three parts, the discussion of a problem situation; the development of the problem situation in the classroom; and clarification of the perceptions about the lived experience. The final considerations point out that the pedagogical practice adopted allowed socio-emotional learning and the habilitation and stimulation of executive functions, such as inhibitory control, cognitive flexibility and working memory.